Knowledge, training and access to global positioning systems: views of young fishermen in Malaysia - Bolong, Jusang; Osman, Nizam; Omar, Siti Zobidah; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril (Canadian Center of Science and Education, 2014)
The main aim of this study is to identify the knowledge around, access to and training for use of a Global Positioning System (GPS) among young fishermen in Malaysia. This is a quantitative study, wherein a total of 240 young fishermen aged between 15 and 40 years old from four fishing areas have been chosen as the respondents. Based on the analyses performed, it can be seen that young fishermen in Malaysia have a good level of knowledge on the potential role GPS could play in their fishing activities. In addition, there is a lack of access to GPS training. A number of recommendations have been placed which, it is a hoped, can be used to further enhance the use of GPS among young fishermen in Malaysia.